Meta-Analysis the Association between Chronic Obstructive Pulmonary Disease Comorbidity and COVID-19 Mortality - Daniyar, Pamogsa Ratri Adha; Kristiyanto, Agus; Rahardjo, Setyo Sri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
disease that hit the world community at the end of 2019. The risk of death from COVID-19 is highly dependent on age and previous health conditions. COVID-19 severe and critical symptoms are more commonly found in older patients and patients who have chronic comor